Going to extremes: Social identity and communication processes associated with gang membership. (November 2014) - Goldman, Liran; Giles, Howard; Hogg, Michael A.
Gang violence, endemic to many communities in the United States and around the world is a very significant social problem. Given that the messages conveyed by, and the rivalries associated with, gang identities readily invoke constructs and processes familiar to the social psychological study of social identity, intergroup relations, and communication (Lauger, 2012), it is surprising that social psychologists have not advanced such an analysis of gangs. In attempt to fill this void and set a research agenda, this theoretical article examines the role social identity and identity-related communication play in promoting affiliation with gangs, particularly among youth who confront uncertainties and strive for family-like protection. The article discusses messaging communicated by gang members and reasons why youth adopt antisocial (e.g., violent) rather than prosocial behaviors. It also explores ways to diminish the allure of gang membership and raises questions for future research.